A160: Role of Interleukin‐1 in Abnormal Monocyte Phenotype in Systemic Onset Juvenile Idiopathic Arthritis. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Zhang, Yujuan; Macaubas, Claudia; Gupta, Saloni; Klein, Clarissa; Pascual, Virginia; Hay, Arielle; Thompson, Susan D.; Sandborg, Christy I.; Ilowite, Norman T.; Mellins, Elizabeth D.
Abstract : Background/Purpose: Monocytes phenotype changes in different microenvironments: the proinflammatory M1, regulatory M2, and M2‐like phenotypes are each regulated by specific transcriptional factors (TFs). We have observed altered phenotypes in blood monocytes in systemic onset juvenile idiopathic arthritis (sJIA), including a decreased M1 cells, an increased mixed M1/M2 cells, and reduced secretion of IL‐1, despite an increased IL‐1b response to LPS (PMID 22281427). Here, we investigate whether these monocyte phenotypes are affected by IL‐1 blockade. We analyzed monocytes from RAPPORT (RA ndomizedP laceboP hase studyO fR ilonacept in theT reatment of sJIA) patients to determine levels of TFs involved in monocyte polarization and expression of genes related to IL‐1 secretion, before and after treatment with Rilonacept, an IL‐1 trap. Methods: Subjects on the Rilonacept arm received active drug from week 0 for a total of 24 weeks; subjects on the placebo arm received placebo for 4 weeks, then Rilonacept for 20 weeks. Blood samples were obtained at week 0, 2, 4, 14 and 24. We used real time PCR to measure M1 associated genes: Interferon Regulatory factor (IRF) family IRF5, STAT1; M2 associated genes IRF4, STAT6, Kruppel‐Like Factor 4 (KLF4) and peroxisome proliferator‐activated receptor‐γ (PPAR‐γ); IL‐1 secretion related genes: RAB39, RAB27A, RAB27B, P2RX7, and IL‐1β. All TFs levels were normalized by the average levels of 3 housekeeping genes. Results: 30 non‐paired RNA samples from 15 subjects were tested. Samples from subjects treated with Rilonacept for ≥10 weeks (Late RAPPORT) showed decreased expression of M2 genes, especially KLF4, compared to those untreated or treated for <10 weeks (Early RAPPORT) (Fig1 ), except for PPAR‐γ. Samples collected when there was clinical improvement also showed reduced KLF4 (Fig2 .). The expression of TFs following IL‐1 inhibition in sJIA patients is distinct from normal controls. Levels of IL‐1 secretion related genes, except for RAB27B, also were reduced in "Late RAPPORT" samples (Fig3 .). Conclusion: IL‐1 blockade in sJIA is likely associated with changes in the activation profile and expression of IL‐1 secretion related genes in circulating monocytes. Monocytes phenotypes in treated subjects are not "normal" and likely reflect changes associated with compensated inflammation.